Conquering the market: The expansion strategies of Santander and BBVA in Latin America - Miguel Angel López-Morell; María Mercedes Bernabé Pérez (The European Association for Banking and Financial History (EABH), 2018)
Three decades ago, and with very few precedents, Spain's two principal banking corporations began an intense process of expansion throughout Latin America. Not only did they compete with one other in this new market, but they also faced competition from domestic Latin American banks and other foreign banks. This paper analyses the key elements that encouraged these two banks to enter the Latin American market. It assesses their success or failure in each country they entered, and in the subcontinent as a whole. Finally, it examines the different strategies they used to achieve their aims.
Keywords: F3; F21; G21; N2; N26; 330; Retailing Banks; Latin America; FDI; Global Banks; Bank Profitability